Visual outcomes following vitrectomy for diabetic retinopathy amongst Indigenous and non‐Indigenous Australians in South Australia and the Northern Territory. (16th November 2017) - Kaidonis, Georgia; Hassall, Mark M; Phillips, Russell; Raymond, Grant; Saha, Niladri; Wong, George HC; Gilhotra, Jagjit S; Liu, Ebony; Burdon, Kathryn P; Henderson, Tim; Newland, Henry; Lake, Stewart R; et al.
Abstract: Importance: Visual outcomes following diabetic vitrectomy have not previously been studied in an Australian population. Background: This analysis aimed to determine the rate of, and factors associated with visual success following diabetic vitrectomy performed for Indigenous and non‐Indigenous Australians, and investigate factors predisposing to early progression to diabetic retinopathy (DR) requiring vitrectomy. Design: Retrospective, population‐based audit. Participants: All patients undergoing vitrectomy for the complications of DR in South Australia (SA) and the Northern Territory (NT) between 2007 and 2011. Methods: Medical records were audited and data collected, including demographics, diabetic history, past treatment for DR, indication for vitrectomy and visual acuity pre and postoperatively. Main Outcome Measures: Visual success (gain of ≥15 ETDRS letters) at 6 and 12 months, postoperatively. Results: A total of 495 diabetic vitrectomies, for 404 eyes of 335 patients were performed in SA and NT between 2007 and 2011. 77 (23%) patients requiring diabetic vitrectomy were Indigenous Australians. 87% of patients undergoing diabetic vitrectomy had stable or improved vision at 1 year, postoperatively. There was no significant difference between indigenous and non‐indigenous eyes achieving visual success ( P  = 0.929). Timely preoperative laser treatment ( P  = 0.03) and preoperative visual acuity ( P  = 0.01) were the predominant factors associated with visual success. Conclusions and Relevance: Indigenous patients are just as likely to have improved vision following diabetic vitrectomy as non‐Indigenous Australians. However, the small subset of indigenous patients with blind eyes prior to vitrectomy are significantly less likely to improve from surgery. The underlying factors associated with poor outcomes in this group requires further exploration.